2020
DOI: 10.5498/wjp.v10.i9.212
|View full text |Cite
|
Sign up to set email alerts
|

Delirium, insulin-like growth factor I, growth hormone in older inpatients

Abstract: BACKGROUND Delirium is a common disorder in elderly medical inpatients with serious adverse outcomes and is characterized by sudden onset, disturbance in attention, awareness, consciousness and cognition, and often with behavioural disturbances. Central to understanding delirium, is understanding mechanisms by which body and brain wellbeing are linked and in particular how brain responses to bodily homeostatic stress is mediated. A number of studies have investigated the relationship between insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…In the present study, our data also indicate that lower IGF-1 and CRH levels are tightly associated with postoperative delirium. Consistent with previous studies, low levels of IGF-1 and high levels of GH are independently associated with the occurrence of delirium (Adamis et al, 2020;Li et al, 2018). Inversely, Chu et al (2016) reported that serum IGF-1 level was nonspecific for predicting POD onset, and IGF-1 level alteration might be regarded as a disease biomarker rather than a risk marker.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, our data also indicate that lower IGF-1 and CRH levels are tightly associated with postoperative delirium. Consistent with previous studies, low levels of IGF-1 and high levels of GH are independently associated with the occurrence of delirium (Adamis et al, 2020;Li et al, 2018). Inversely, Chu et al (2016) reported that serum IGF-1 level was nonspecific for predicting POD onset, and IGF-1 level alteration might be regarded as a disease biomarker rather than a risk marker.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, as it was reported in the introduction, frailty/ sarcopenia is a risk factor for delirium in medical elderly patients [35][36][37] but also in patients who have undergone colorectal cancer surgery [54]. Besides, a disturbed GH/ IGF-1 axis was found in delirium [34].…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, it has been suggested that sarcopenia precedes the onset of frailty and that it is not only due to the ageing process but also to inflammatory mechanisms [33]. Interestingly, studies have also indicated that sarcopenia (cachexia/frailty) is a risk factor for delirium in colorectal cancer surgery [34], and in medical cohorts [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Patients were recruited according to the following criteria: 1) glioma as primary tumor and 2) OS > 30 days. Patients with missing information were excluded and those with an incomplete pattern were subjected to missing completely at random testing using Little’s method ( Adamis et al, 2020 ). These criteria and statistical analyses were applied to both TCGA and CGGA data.…”
Section: Methodsmentioning
confidence: 99%